Power Profiles of Competitive and Noncompetitive Mountain Bikers. Issue 2 (February 2019) - Novak, Andrew R.; Bennett, Kyle J.M.; Pluss, Matthew A.; Fransen, Job; Watsford, Mark L.; Dascombe, Ben J.
Abstract : Abstract: Novak, AR, Bennett, KJM, Pluss, MA, Fransen, J, Watsford, ML, and Dascombe, BJ. Power profiles of competitive and noncompetitive mountain bikers. J Strength Cond Res 33(2): 538–543, 2019—The performance of Olympic distance cross-country mountain bikers (XCO-MTB) is affected by constraints such as erosion of track surfaces and mass start congestion which can affect race results. Standardized laboratory assessments quantify interseasonal and intraseasonal cycling potential through the assessment of multiple physiological capacities. Therefore, this study examined whether the power profile assessment (PPA) could discriminate between competitive XCO-MTB and noncompetitive mountain bikers (NC-MTB). Second, it aimed to report normative power profile data for competitive XCO-MTB cyclists. Twenty-nine male participants were recruited across groups of XCO-MTB ( n = 14) and NC-MTB ( n = 15) mountain bikers. Each cyclist completed a PPA that consisted of increasing duration maximal efforts (6, 15, 30, 60, 240, and 600 seconds) that were interspersed by longer rest periods (174, 225, 330, 480, and 600 seconds) between efforts. Normative power outputs were established for XCO-MTB cyclists ranging between 13.8 ± 1.5 W·kg −1 (5-second effort) and 4.1 ± 0.6 W·kg −1 (600-second effort). No differences in absolute peak power or cadence were identified between groups across any effort length ( p > 0.05). However, the XCO-MTB cyclists produced greater mean power outputs relative to body mass than the NC-MTB during the 60-second (6.9 ± 0.8 vs 6.4 ± 0.6 W·kg −1 ; p = 0.002), 240-second (4.7 ± 0.7 vs. 3.8 ± 0.4 W·kg −1 ; p < 0.001), and 600-second (4.1 ± 0.6 vs. 3.4 ± 0.3 W·kg −1 ; p < 0.001) efforts. The PPA is a useful discriminative assessment tool for XCO-MTB and highlights the importance of aerobic power for XCO-MTB performance.